Gradient Microstructure Induced by Surface Mechanical Attrition Treatment in Grade 2 Titanium Studied Using Positron Annihilation Spectroscopy and Complementary Methods - Konrad Skowron (MDPI AG, 2021)
Microstructural changes in grade 2 titanium generated by surface mechanical attrition treatment (SMAT) were studied using positron annihilation lifetime spectroscopy and complementary methods. A significant increase in the mean positron lifetime indicated many lattice defects introduced by SMAT. Two positron lifetime components were resolved in the positron lifetime spectra measured. The longer lifetime revealed the presence of vacancy clusters containing about 3 or 4 vacancies, while the shorter one was attributed to the annihilation of positrons trapped at dislocations. The changes of the positron lifetime indicated a decreasing dislocation density and the presence of a deeper layer with a higher concentration of vacancy clusters at the distance from the treated surface for which the microhardness approached the value for the strain-free matrix. Electrochemical impedance spectroscopy showed the positive effect of SMAT on the corrosion resistance of the titanium studied in a saline environment also after removal of the original oxide layer that was formed during the SMAT.